2012
DOI: 10.6090/jarq.46.237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Metabolite Alteration under Flooding Stress in Soybeans

Abstract: Soybean is a crop known to be susceptible to flooding and enhancing flooding tolerance may be a workable strategy to improve soybean production. To elucidate the effects of flooding on soybean metabolism, metabolite alterations in seedlings during flooding treatment were identified using capillary electrophoresis-mass spectrometry (CE/MS). The principal component analysis (PCA) of soybean seedlings revealed that the first component accounted for 62.2% of total variance, and the alteration of metabolites in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 62 publications
3
33
0
Order By: Relevance
“…It is well established that Ala and GABA accumulate in different plant organs as a consequence of oxygen deficiency of different grades imposed by either waterlogging or submergence (Branco-Price et al, 2008;Mustroph et al, 2009Mustroph et al, , 2010Narsai et al, 2009Narsai et al, , 2011van Dongen et al, 2009;Rocha et al, 2010a;Nakamura et al, 2012;Barding et al, 2013). In line with these reports, we observed an accumulation of Ala and GABA in roots of wild-type Arabidopsis under long-term hypoxia.…”
Section: Loss Of Function Of Gox3 Induces Metabolic Rearrangements Insupporting
confidence: 80%
“…It is well established that Ala and GABA accumulate in different plant organs as a consequence of oxygen deficiency of different grades imposed by either waterlogging or submergence (Branco-Price et al, 2008;Mustroph et al, 2009Mustroph et al, , 2010Narsai et al, 2009Narsai et al, , 2011van Dongen et al, 2009;Rocha et al, 2010a;Nakamura et al, 2012;Barding et al, 2013). In line with these reports, we observed an accumulation of Ala and GABA in roots of wild-type Arabidopsis under long-term hypoxia.…”
Section: Loss Of Function Of Gox3 Induces Metabolic Rearrangements Insupporting
confidence: 80%
“…Irrespective of morphotypes, three sugar metabolic pathways were enhanced in the root system of L. grandiflora grown in the terrestrial condition (starch and sugar metabolism, galactose metabolism, and amino sugar and nucleotide sugar metabolic pathways). In organs of wetland plant species, reserves of carbohydrates and ethanol fermentation are equally important in maintaining glycolysis and energetic metabolism in general (reviewed in Nakamura et al., ). In our study, the significant decrease in glucose‐6‐phosphate and fructose‐6‐phosphate levels measured in both morphotypes, and the concomitant increase in fructose and mannose concentrations pinpointed the enhanced glycolytic activities and energetic needs of plants developing in terrestrial condition.…”
Section: Discussionmentioning
confidence: 99%
“…Some enzymatic changes also occur in the tricarboxylic acid (TCA) cycle leading to important changes favoring plant survival of anaerobic conditions (Fox and Kennedy, 1991; Fox et al, 1994; Fan et al, 2003; Howell et al, 2006; Nakamura et al, 2012). Fox and Kennedy (1991) reported that 2-oxoglutarate dehydrogenase activity decreased under anoxia and the conversion of 2-oxoglutarate to succinate was identified as the limiting step in the TCA cycle under these conditions.…”
Section: Adjustments Of Carbohydrate Metabolism Under Low Oxygenmentioning
confidence: 99%